2011
DOI: 10.3821/1913-701x-144.3.125
|View full text |Cite
|
Sign up to set email alerts
|

Practice Change Challenges and Priorities: A National Survey of Practising Pharmacists

Abstract: Background: Vision and action plans have been created to address the future of pharmacy and help pharmacists progress into expanded roles in order to provide more patient-centred care. To assess the thoughts and perceptions of pharmacists in these new roles, a survey was conducted among practising pharmacists in Canada. Methods: A Web-based survey, developed as part of the Canadian Pharmacists Association's Moving Forward initiative, was open to all practising pharmacists in September and October of 2007. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 6 publications
3
39
0
Order By: Relevance
“…The initial pool of barriers items were identified by previous studies [14][15][16][17][18][19][20]. Modifications were done to make it convenient with the UAE practice setting.…”
Section: Methodsmentioning
confidence: 99%
“…The initial pool of barriers items were identified by previous studies [14][15][16][17][18][19][20]. Modifications were done to make it convenient with the UAE practice setting.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] However, advancement toward this objective has been slow and incomplete. [4][5][6][7][8][9] For example, a survey conducted in 2007 found that the majority of pharmacist respondents spent their work time on dispensingrelated activities, although they were interested in and recognized the need for practice change. 7 British Columbia pharmacists have had the authority to adapt prescriptions since 2009 8 ; however, adapted prescriptions accounted for only 0.2% of all prescription claims in that year.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] For example, a survey conducted in 2007 found that the majority of pharmacist respondents spent their work time on dispensingrelated activities, although they were interested in and recognized the need for practice change. 7 British Columbia pharmacists have had the authority to adapt prescriptions since 2009 8 ; however, adapted prescriptions accounted for only 0.2% of all prescription claims in that year. 9 In Alberta, pharmacists have been allowed to apply for additional prescribing authorization since 2007, 10 but only 215 of the roughly 4000 pharmacists in the province have received this authority (D Cooney, Deputy Registrar, Alberta College of Pharmacists; personal communication by e-mail, January 24, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…1 To meet the challenges in the shift from a product focus to a patient focus, pharmacists have expressed a need for additional education and training. 2 To be responsive to pharmacists' new roles in pharmacy practice, continuing education (CE) in pharmacy must also change and be refocused.…”
Section: Introductionmentioning
confidence: 99%